A novel colour image encryption based on fractional order Lorenz system. (3rd May 2021) - Li, Shixu; Yu, Yongjin; Ji, Xingquan; Sun, Qi
Abstract : A colour image encryption algorithm based on fractional Lorenz system has been developed in this paper. Firstly, the colour image has been divided into three layers: R, G, and B, and Arnold map has been used for scrambling the three layers separately, and the plaintext pixel has been selected as the scrambling parameter. The Tent map has been used to associate the plain text to generate the initial values of the fractional Lorenz system, which has been iterated by the system to generate a pseudo-random sequence that can be used for two pixel diffusions. The first pixel diffusion is to diffuse the pixels of each layer to the other two layers, and the second pixel diffusion is to add modulus diffusion inside the layer. Simulation results illustrate that the plaintext image is encrypted into a meaningless noise image. The superior performance of proposed algorithm has been proved by the key space analysis, histogram analysis, correlation test, sensitivity analysis and information entropy analysis, and it can resist various common attack methods.